The Endurance of Palestinian Political Factions An Everyday Perspective from Nahr el-Bared Camp - Issa, Perla (University of California Press, 2021)
The Endurance of Palestinian Political Factions is an ethnographic study of Palestinian political factions in Lebanon through an immersion in daily home life. Perla Issa asks how political factions remain the center of political life in the Palestinian camps in the face of mounting criticism. Through an examination of the daily, mundane practices of refugees in Nahr el-Bared camp in particular, this book shows how intimate, interpersonal, and kin-based relations are transformed into political networks and offers a fresh analysis of how those networks are in turn metamorphosed into political structures. By providing a detailed and intimate account of this process, this book reveals how factions are produced and reproduced in everyday life despite widespread condemnation. "Utilizing rich ethnographic fieldwork, Perla Issa provides an engaging analysis of Palestinian factions in the refugee camp of Nahr el-Bared. Her book illuminates the centrality of political factions to quotidian social interactions and the rhythms of everyday life." Adam Hanieh, author of Money, Markets, and Monarchies: The Gulf Cooperation Council and the Political Economy of the Contemporary Middle East "How do political factions maintain centrality in Palestinian political life even when they are widely unpopular and even delegitimized? How are such factions reproduced in the face of widespread condemnation? The questions that animate this manuscript are vitally important." Ilana Feldman, author of Life Lived in Relief: Humanitarian Predicaments and Palestinian Refugee Politics